Expanding the Scope of Health Information Systems - Kuhn, K. A.; Giuse, D. A.; Lapão, L.; Wurst, S. H. R. (Methods of Information in Medicine, 2007)
Objectives: To identify current developments, obstacles, and opportunities for health information systems.Methods: International reports werediscussed during an IMIA HIS Working Conference with a focus on architectural design, project goals and drivers, obstacles, and opportunities.Results: Technology and standards are available to build regional and national health IT networks, and successful implementations are currently being realized. There is, however, little consensus and communication concerning goals, benefits and risks of large-scale health IT initiatives. Complexity tends to be underestimated, and the public needs to be more involved in the decision-making process.Conclusion: On all levels and across borders, a climate of exchange of ideas, experiences – both successes and failures-, policies, standards, systems, and information should be created.
Keywords: Health information systems; eHealth